PENDIDIKAN PONDOK PESANTREN TRADISONAL DALAM PERSEPKTIF PENDIDIKAN ISLAM INDONESIA - Kosim, Nanang (STAI Darul Qalam Tangerang, 2024)
Whether it is recognized or not, Islamic boarding schools are the oldest educational institutions that have been attached to the journey of Indonesian life since hundreds of years ago and have made many significant contributions to the development of this nation, so it is not surprising that education experts such as Ki Hajar Dewantoro and Dr. Soetomo once aspired to the Islamic boarding school education system model as a national education model. For them, the pesantren education model is an intelligent creation of Indonesian culture that has character and should be maintained and developed. Because many things have not been explored from the education of traditional Islamic boarding schools in the perspective of Indonesian Islamic education, this research was conducted. Specifically, this study aims to describe Traditional Islamic Boarding School Education in the Perspective of Indonesian Islamic Education, describe the vision and mission of traditional Islamic boarding school education, describe the traditional Islamic boarding school education curriculum, and describe the management of traditional Islamic boarding school education The results of this study show (1) that in the perspective of Indonesian Islamic education, traditional Islamic boarding school education is a part of the Separate from national education that provides enlightenment for students integrally, both cognitive (knowlagde), affective (attucude) and psychomotor (skill), (2) That the vision and mission of traditional Islamic boarding school education in the perspective of Indonesian Islamic education are: First, emphasizing the principles of asasul khomsah or five souls, namely sincerity, simplicity, independence, ukuwah islamiyah and freedom. Second, the pattern of kiai relations with students is not only physical, but also inward. Third, Islamic boarding school education, in addition to being directed at the transmission of Islamic knowledge, the maintenance of Islamic traditions and the reproduction of ulama', is also intended to be an alternative for People centered development, Value oriented development, Institution development and Self reliance and sustainability. (3) That the current traditional Islamic boarding school education curriculum does not only focus on our classic books (read: religious science), but also includes more and more general subjects and skills, currently in Islamic boarding school education the science is starting to be unpopular. (4) In terms of institutional management, in the current traditional Islamic boarding school educational institutions, there has been a fundamental change, namely from centralistic, hierarchical and tendency to single fighter leadership to a collective management model such as the foundation model. The recommendations in this study are (1) because the role of traditional Islamic boarding school educational institutions is very important in answering the spiritual crisis of modern humans, or at least as a balance to the tendency of hedonistic lifestyles and dishonesty, its existence needs to receive more serious support from all parties. (2) Because human success is more determined by EQ and SQ factors, while SQ is the main aspect that is the focus of traditional Islamic boarding school education, it is recommended to all parties to continue to develop heart education in order to obtain true life success. (3)Because the educational activities of traditional Islamic boarding schools since its inception have been able to develop positively in society and even have a vital contribution not only in the theological dimension but also social as the main locomotive in the enlightenment of the community, then of course it is a treasure and national wealth that should be preserved in this beloved archipelago